Warming and monsoonal climate lead to large export of millennial-aged carbon from permafrost catchments of the Qinghai-Tibet Plateau. (22nd June 2020) - Song, Chunlin; Wang, Genxu; Haghipour, Negar; Raymond, Peter A
Abstract: Permafrost carbon pool destabilization causes substantial fluvial export of soil carbon, yet the export patterns and magnitudes are not well understood. Here we investigated the radiocarbon ( 14 C) in dissolved organic and inorganic carbon (DOC and DIC, respectively) exported from a mid-sized river in the central Qinghai-Tibet Plateau (QTP) permafrost region. We utilized the radiocarbon dating technique to reveal the ages of riverine dissolved carbon and a statistical model to partition the riverine carbon from different age categories. DOC and DIC showed bomb-depleted 14 C signatures corresponding to millennial ages. Seasonally, 14 C-depleted DOC and DIC ages were associated with active layer thaw and flow path deepening. Spatially, older DOC and DIC were found in the valley sites correlated with warmer permafrost and higher groundwater flow. Further, isotopic mixing models suggested that 83 ± 27% of riverine DOC was derived from active layer and permafrost layer aged carbon. DIC export was comprised of a smaller portion of aged carbon (47.3 ± 2.6%) but a much larger flux of aged carbon due to higher annual DIC export. Interestingly, approximately 56% of annual aged DOC and DIC were exported in the short summer season (July to September). The monsoon climate-induced overlap of high discharge and maximum active layer thaw depth in summer enhanced the remarkably rapid fluvial export of millennial-aged carbon. Annual aged carbon yields in YRSR (275 ± 90 and 1661 ± 91 kg km −2 yr −1 for DOC and DIC, respectively) are much larger than those of Kolyma River (160 ± 89 and 234 ± 105 kg km −2 yr −1 for DOC and DIC, respectively). These results suggest a unique old carbon loss pattern in the QTP permafrost region compared to higher latitude permafrost regions with a non-monsoonal climate. As climate warms, more old carbon export is expected, which may affect the permafrost carbon pool and the river biogeochemical processes.